STRATEGIC GUIDELINES FOR COMBATING CLIMATE CHANGE AND THREATS IN GLOBAL ENVIRONMENTAL SECURITY - Lyudmila Levkovska; Alla Omelchenko (Economics & Education, 2021)
It is substantiated that the development of scientific and technological progress since the middle of the last century has led to intensive industrialization that, together with globalization processes, has resulted in global climate change. Nowadays, combating global warming is one of the most challenging and urgent tasks of humanity. Sweeping changes in natural systems, primarily an increase in the frequency and duration of droughts, floods, melting glaciers and rising water in the seven seas, biodiversity loss, etc., are the effect of global temperature rise. There is also a deterioration of living conditions and standards of the public, declining food security, especially in low- and middle-income countries. The research outlines the main trends in climate change. It is clarified the impact of climate change on the environment, man, society, and economy. The authors emphasize the significance and role of local actions towards adapting to the effects of climate change, which may become a tool for reducing climate risks in a global environment. It is justified that the challenge of climate change is addressed by joint efforts of each state of the world economic space. The effects of climate change and adaptation measures within economic realms are regarded by relying on global experience. The purpose of the article is to determine strategic guidelines for implementing adaptation measures to the impact of climate change to guarantee global environmental security. The research is based on a systems approach to solving the issue of guaranteeing global environmental security. In this context, it refers to the stimulation of constant economic modernization and the development of a new economic structure of the 21st century aimed at searching for effective mechanisms and tools promoting the measures for reducing greenhouse gas emissions. First of all, this means the implementation of energy-saving technologies, which will reduce the energy intensity of production and thus, increase economic energy efficiency and enhance global environmental security.